Filial Value among Caregivers of Schizophrenia Patients in Outpatient unit of Menur Mental Hospital Surabaya, Indonesia - ayesie natasa; Ah. Yusuf; Hanik Endang Nihayati; Ely Rahmatika Nugrahani; Nurilla Kholidah; Dwi Indah Lestari (International Journal of Nursing and Health Services (IJNHS), 2020)
The filial value from the caregiver of schizophrenic patients began to shift due to social changes and the burden of care experienced. The purpose of this study to describe the characteristics and caregiver filial value of schizophrenic patients. : Research design used a descriptive study with a cross-sectional approach. The sampling technique used was quota sampling. 200 schizophrenic patients caregiver in the outpatient unit of the mental hospital menur recruited in the study according to the inclusion criteria. Data collection used a questionnaire developed from caring Swanson. Most caregivers showed good filial value. The filial value was described by maintaining belief, knowing, being with doing for, and enabling. This attitude supported care for schizophrenic patients. Filial value caregiver schizophrenic patients in menur mental hospital outpatient units support in the treatment of ongoing schizophrenic patients. Risk management for social change was needed to maintain filial value caregivers